Analysis of neuron–astrocyte metabolic cooperation in the brain of db/db mice with cognitive decline using 13C NMR spectroscopy. Issue 1 (January 2017) - Zheng, Hong; Zheng, Yongquan; Wang, Dan; Cai, Aimin; Lin, Qiuting; Zhao, Liangcai; Chen, Minjiang; Deng, Mingjie; Ye, Xinjian; Gao, Hongchang
Type 2 diabetes has been linked to cognitive impairment, but its potential metabolic mechanism is still unclear. The present study aimed to explore neuron–astrocyte metabolic cooperation in the brain of diabetic ( db/db, BKS.Cg-m +/+ Leprdb/J) mice with cognitive decline using 13 C NMR technique in combination with intravenous [2- 13 C]-acetate and [3- 13 C]-lactate infusions. We found that the 13 C-enrichment from [2- 13 C]-acetate into tricarboxylic acid cycle intermediate, succinate, was significantly decreased in db/db mice with cognitive decline compared with wild-type (WT, C57BLKS/J) mice, while an opposite result was obtained after [3- 13 C]-lactate infusion. Relative to WT mice, db/db mice with cognitive decline had significantly lower 13 C labeling percentages in neurotransmitters including glutamine, glutamate, and γ-aminobutyric acid after [2- 13 C]-acetate infusion. However, [3- 13 C]-lactate resulted in increased 13 C-enrichments in neurotransmitters in db/db mice with cognitive decline. This may indicate that the disturbance of neurotransmitter metabolism occurred during the development of cognitive decline. In addition, a reduction in 13 C-labeling of lactate and an increase in gluconeogenesis were found from both labeled infusions in db/db mice with cognitive decline. Therefore, our results suggest that the development of cognitive decline in type 2 diabetes may be implicated to an unbalanced metabolism in neuron–astrocyte cooperation and an enhancement of gluconeogenesis.